2012
DOI: 10.1016/j.ijrobp.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Prone Whole-Breast Irradiation Using Three-Dimensional Conformal Radiotherapy in Women Undergoing Breast Conservation for Early Disease Yields High Rates of Excellent to Good Cosmetic Outcomes in Patients With Large and/or Pendulous Breasts

Abstract: Purpose To report our institution’s experience using prone positioning for three-dimensional conformal radiotherapy (3D-CRT) to deliver post-lumpectomy whole breast irradiation (WBI) in a cohort of women with large and/or pendulous breasts, to determine the rate of acute and late toxicities and, more specifically, cosmetic outcomes. We hypothesized that using 3D-CRT for WBI in the prone position would reduce or eliminate patient and breast size as negative prognostic indicators for toxicities associated with W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 35 publications
3
42
1
Order By: Relevance
“…grade 2-3 late toxicity was reported in 4.4% (skin) and 13.7% (subcutaneous tissues) of patients. These rates are comparable with those reported by Bergom et al (14) in 110 patients with large or pendulous breasts: 11% of patients had grade 2 late toxicities, including grade 3 induration/ fibrosis in 2%. The largest patient cohort was presented in the study by the group at the New York School of Medicine, who treated about 400 patients with prone WBI, including an integrated boost (15).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…grade 2-3 late toxicity was reported in 4.4% (skin) and 13.7% (subcutaneous tissues) of patients. These rates are comparable with those reported by Bergom et al (14) in 110 patients with large or pendulous breasts: 11% of patients had grade 2 late toxicities, including grade 3 induration/ fibrosis in 2%. The largest patient cohort was presented in the study by the group at the New York School of Medicine, who treated about 400 patients with prone WBI, including an integrated boost (15).…”
Section: Discussionsupporting
confidence: 89%
“…The photographs were scored by 2 medical students and 1 radiation oncologist in training. Still, the cosmetic outcome is in line with published prone (14,15) and supine data (25,27), and the most obvious explanation is that the differences are not perceived as worse cosmetic outcome when scored subjectively. Although Cardoso et al (28) reported a fair concordance between the BCCT.core software and a subjective evaluation using the Harvard scale, in our data set the software scored significantly worse than the 3 observers, both on the photograph with the arms down (PZ.007) and on the photograph with the arms up (P<.001).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…kV imaging was consecutively taken to evaluate the positioning in DIBH. Multiple breath hold CBCT has been described in lung carcinoma [33] and is a potentially more accurate setup verification procedure. Interruption of the CBCT gantry rotation is, to our knowledge, not possible with our Elekta XVI software.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Even though prone set-up is considered a reasonable option for large breasted patients, it, however, requires patients' compliance and some older patients may not be able to maintain the position. Additionally, in our series 63.0% of patients had a BMI .30% and 94.3% had a BMI .25.…”
Section: Discussionmentioning
confidence: 99%